2016
DOI: 10.30935/cedtech/6178
|View full text |Cite
|
Sign up to set email alerts
|

How Students Communicate Mathematical Ideas: An Examination of Multimodal Writing Using Digital Technologies

Abstract: This article reports the findings of a study designed to examine the influence of multimodal writing on the communication of mathematical ideas. Elementary school students (ages 8-13) were required to write mathematics notes using two digital writing technologies, a personal digital notepad and a social mathematics blog, in the context of a formal intervention. Fortytwo students participated, across three schools. The study showed that when students wrote notes that could be assessed for correctness, their ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
6
17
0
6
Order By: Relevance
“…It showed that the student coordinated in written form by mathematical expression. It is in line with Freeman, Higgins, & Horney (2016) that written mathematics communication could facilitate students with low level to improve their concepts.…”
Section: Discussionsupporting
confidence: 58%
“…It showed that the student coordinated in written form by mathematical expression. It is in line with Freeman, Higgins, & Horney (2016) that written mathematics communication could facilitate students with low level to improve their concepts.…”
Section: Discussionsupporting
confidence: 58%
“…Previous studies have supported this conclusion. In the studies, it was stated that students explain their reasoning, correctness of solutions, thinking processes by writing and they made reflections about mathematics learning process in mathematics courses (Freeman et al, 2016;Inoue & Buczynski, 2011). Suhaimi et al (2016) stated that students who write journal in mathematics courses organize their thoughts, thus journal writing improves communication and critical thinking skills of the students.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…One of the strategies used in the development of RT skills is "Writing". Writing is an effective tool for students to express, explore, organize, and reflect ideas about mathematical content and process (Freeman, Higgins & Horney, 2016;Inoue & Buczynski, 2011;Suhaimi, Shahrill, Tengah & Abbas, 2016). With "Journal writing", which is one of the writing activities, students can reflect on their experiences, points they are strong or weak, important points of an event, how they deal with a power situation, and their feelings (Farrah, 2012;Guce, 2017Guce, , 2018Mitchell & Coltrinari, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Writing mathematical ideas provided a way for students to gain insight about abstract concepts through drawing and other means of creative expression and experiments. It also allowed students to communicate their ideas to others, including their teachers and friends [6]. Mathematically, the results of group discussions used the concept of a reasonable and clear relationship, and were arranged logically and systematically.…”
Section: Using Mathematical Language To Show Mathematical Ideas Appromentioning
confidence: 99%